SOCIAL BEHAVIOR PARADIGM ‎ AND SOCIAL EXCHANGE BEHAVIORISTIC APPROACH - Aspandi Aspandi (Dirosatuna: Journal of Islamic Studies, 2020)
The sociology paradigm gave birth to a variety of paradigms including; the paradigm of social facts, the paradigm of social definition and the paradigm of social behavior. In contrast to the two previous paradigms, the paradigm of social behavior focuses its discussion on the relationship of individuals and their environment in social interactions and their repetition. The paradigm of social behavior was born as a critique of the paradigm of social facts and social definitions as a perspective that is mystical, cannot be explained rationally and is considered unscientific. The paradigm of social behavior develops in "social behaviorism" with two main supporting theories namely Behavioral Sociology and Theory Exchange theories. The behaviorism approach was developed by B.F Skinner who tried to translate the psychological principles of behaviorism flow into sociology. The Exchange approach, developed by George C Homans, is a correction of structural functionalism that focuses on the determinism of social structure and underestimates the position of individuals as actors. The main characteristic of this theory lies in its analysis of social relations according to cost and reward. This type of research is qualitative in the form of library research. By using various methods such as analytic language, comparative, inductive, it is expected to be able to construct a concept of social behavior paradigm comprehensively.